Multivalent rituximab lipid nanoparticles as improved lymphoma therapies: indirect mechanisms of action and in vivo activity. (November 2011) - Popov, Jesse; Kapanen, Anita I; Turner, Christopher; Ng, Rebecca; Tucker, Catherine; Chiu, Gigi; Klasa, Richard; Bally, Marcel B; Chikh, Ghania
Aims: The activity of therapeutic antibodies can be enhanced by creating multivalent constructs, such as antibody lipid nanoparticles (LNPs). Here, we examine differences between rituximab (Ritux) and Ritux-LNPs in terms of their indirect mechanisms of action: complement-dependent cytotoxicity (CDC) and antibody-dependent cell-mediated cytotoxicity (ADCC).Materials & Methods: We employed two mantle-cell lymphoma cell lines, Z138 and JVM2, which exhibit different in vivo sensitivities to Ritux along with variable expression levels of cell-surface proteins that regulate ADCC and CDC.Results: In both cell lines, CDC and ADCC were found to be significantly enhanced after treatment with Ritux-LNPs compared with Ritux. In vivo efficacy studies, however, suggested that the therapeutic activities of Ritux and Ritux-LNPs were equivalent, which was subsequently explained in part by pharmacokinetic studies indicating rapid elimination of Ritux-LNP.Conclusion: Although indirect and direct mechanisms of multivalent Ritux are enhanced, its further development requires methods to improve its circulation lifetime.